2021
DOI: 10.1186/s12889-021-10633-y
|View full text |Cite
|
Sign up to set email alerts
|

Supporting employees with chronic conditions to stay at work: perspectives of occupational health professionals and organizational representatives

Abstract: Background Supporting employees with chronic conditions can prevent work-related problems and facilitate sustainable employment. Various stakeholders are involved in providing support to these employees. Understanding their current practices and experienced barriers is useful for the development of an organizational-level intervention to improve this support. The aim of this study was to explore the current practices of occupational physicians and organizational representatives, identifying bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Furthermore, Reibis et al highlights, in a review addressing determinants of reintegration of patients experiencing acute coronary syndrome, a need to pay special attention towards patients with physically demanding jobs and how stepwise reintegration is a supportive return-to-work strategy 10. Additionally, we found that acceptance and understanding from colleagues and employers are beneficial for work resumption, which corresponds well with other studies showing that social relations at the workplace are important for re-employment 41…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, Reibis et al highlights, in a review addressing determinants of reintegration of patients experiencing acute coronary syndrome, a need to pay special attention towards patients with physically demanding jobs and how stepwise reintegration is a supportive return-to-work strategy 10. Additionally, we found that acceptance and understanding from colleagues and employers are beneficial for work resumption, which corresponds well with other studies showing that social relations at the workplace are important for re-employment 41…”
Section: Discussionsupporting
confidence: 88%
“… 10 Additionally, we found that acceptance and understanding from colleagues and employers are beneficial for work resumption, which corresponds well with other studies showing that social relations at the workplace are important for re-employment. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, collaboration between these two domains needs improvement. To improve the collaboration, the first step is to raise awareness among GPs on the relation between health complaints and work, to train GPs to be more able to discuss work-related problems, and to refer patients more easily to an OP [ 28 , 31 , 32 , 34 ]. The second step is to explore initiatives to improve the collaboration, by for example addressing misconceptions between GPs and OPs roles and independence of OPs and how to reach and communicate effectively with each other [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, employees in this study perceived that managers were “at odds” with the government’s recommendations, mainly due to a lack of knowledge concerning laws and regulations. An underlying cause for this conflict may be the complexity and the ambiguity of the published guidelines, combined with the manager’s limited experience in dealing with the current changes in employment laws and policies [ 107 , 121 ]. Another important finding was that the manager was not always aware of the relevant resources, services or useful strategies that could be applied in the workplace.…”
Section: Discussionmentioning
confidence: 99%